The glycoprotein CD147 defines miRNA‐enriched extracellular vesicles that derive from cancer cells - Song Yi Ko; WonJae Lee; Melanie Weigert; Eric Jonasch; Ernst Lengyel; Honami Naora (Journal of Extracellular Vesicles, 2023)
Abstract Extracellular vesicles (EVs) are ideal for liquid biopsy, but distinguishing cancer cell‐derived EVs and subpopulations of biomarker‐containing EVs in body fluids has been challenging. Here, we identified that the glycoproteins CD147 and CD98 define subpopulations of EVs that are distinct from classical tetraspanin+ EVs in their biogenesis. Notably, we identified that CD147+ EVs have substantially higher microRNA (miRNA) content than tetraspanin+ EVs and are selectively enriched in miRNA through the interaction of CD147 with heterogeneous nuclear ribonucleoprotein A2/B1. Studies using mouse xenograft models showed that CD147+ EVs predominantly derive from cancer cells, whereas the majority of tetraspanin+ EVs are not of cancer cell origin. Circulating CD147+ EVs, but not tetraspanin+ EVs, were significantly increased in prevalence in patients with ovarian and renal cancers as compared to healthy individuals and patients with benign conditions. Furthermore, we found that isolating miRNAs from body fluids by CD147 immunocapture increases the sensitivity of detecting cancer cell‐specific miRNAs, and that circulating miRNAs isolated by CD147 immunocapture more closely reflect the tumor miRNA signature than circulating miRNAs isolated by conventional methods. Collectively, our findings reveal that CD147 defines miRNA‐enriched, cancer cell‐derived EVs, and that CD147 immunocapture could be an effective approach to isolate cancer‐derived miRNAs for liquid biopsy.